2020
DOI: 10.3390/ma13122837
|View full text |Cite
|
Sign up to set email alerts
|

Structure Dependence of Poisson’s Ratio in Cesium Silicate and Borate Glasses

Abstract: In glass materials, Poisson’s ratio (ν) has been proposed to be correlated with a variety of features, including atomic packing density (Cg), liquid fragility (m), and network connectivity. To further investigate these correlations in oxide glasses, here, we study cesium borate and cesium silicate glasses with varying modifier/former ratio given the difference in network former coordination and because cesium results in relatively high ν compared to the smaller alkali modifiers. Within the binary glass series,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
2
3
0
Order By: Relevance
“…The high stiffness of the L‐H‐M and L‐H‐M‐AC glasses was determined by nanoindentation studies, [37, 38] which revealed that their Vickers microhardness values were 11.9 and 22.2 GPa, respectively (Figure 3f and S12c), which were comparable to those of some reported metallic glasses [39–41] . Besides, the two SMGs exhibited the Poisson's ratio ( ν ) of 0.3 (less than an abrupt brittle‐to‐ductile transition at ν =0.32 for various glassy systems), [42, 43] just like most oxide glasses, which were prone to undergo a high degree of densification during indentation [44] …”
Section: Resultssupporting
confidence: 82%
“…The high stiffness of the L‐H‐M and L‐H‐M‐AC glasses was determined by nanoindentation studies, [37, 38] which revealed that their Vickers microhardness values were 11.9 and 22.2 GPa, respectively (Figure 3f and S12c), which were comparable to those of some reported metallic glasses [39–41] . Besides, the two SMGs exhibited the Poisson's ratio ( ν ) of 0.3 (less than an abrupt brittle‐to‐ductile transition at ν =0.32 for various glassy systems), [42, 43] just like most oxide glasses, which were prone to undergo a high degree of densification during indentation [44] …”
Section: Resultssupporting
confidence: 82%
“…The high stiffness of the L‐H‐M and L‐H‐M‐AC glasses was determined by nanoindentation studies, [37, 38] which revealed that their Vickers microhardness values were 11.9 and 22.2 GPa, respectively (Figure 3f and S12c), which were comparable to those of some reported metallic glasses [39–41] . Besides, the two SMGs exhibited the Poisson's ratio ( ν ) of 0.3 (less than an abrupt brittle‐to‐ductile transition at ν =0.32 for various glassy systems), [42, 43] just like most oxide glasses, which were prone to undergo a high degree of densification during indentation [44] …”
Section: Resultssupporting
confidence: 82%
“…[39][40][41] Besides, the two SMGs exhibited the Poisson's ratio (ν) of 0.3 (less than an abrupt brittle-to-ductile transition at ν = 0.32 for various glassy systems), [42,43] just like most oxide glasses, which were prone to undergo a high degree of densification during indentation. [44] The multicolored persistent photoemissions of the bulk SMGs were studied via both prompt and delayed (acquired after 1 ms of excitation) photoluminescence (PL) tests at R.T. It was shown that the transparent L-H-M and L-H-M-AC glasses displayed intense RTP bands at ca.…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Strongly interconnected glass networks with low atomic packing density often exhibit lower Poisson's ratio as compared to more densely packed glasses with a lower degree of cross-linking. 29 Although the universal validity of these simplistic correlations has very recently been questioned, 59 the atomic packing density and network dimensionality have frequently been utilized as useful metrics to describe compositional variations in Poisson's ratio for a variety of silicate 48,[60][61][62][63][64] and aluminosilicate glasses. [65][66][67] The observed increase of with increasing molar ratio R may originate from the parallel increase of C g upon progressive substitution of Na 2 O by K 2 O.…”
Section: Properties Of Bulk Reference Glassesmentioning
confidence: 99%